KONSEP ISTIṬĀ’AH DALAM AL-QUR’AN DAN IMPLIKASINYA TERHADAP KESIAPAN IBADAH HAJI DI KENDARI - Muh Rezky Alsyah Ananta; Irdawati Saputri; Mir'atul Hasanah (IAIN KENDARI, 2025)
The Hajj pilgrimage is the fifth pillar of Islam, requiring istitha'ah (capability) asa mandatory prerequisite for pilgrims. This research aims to analyze the meaningof istitha'ah in the Qur'an and its implications for Hajj readiness amongprospective pilgrims in Kendari, Southeast Sulawesi. Employing a qualitativedescriptive-interpretive approach, the research integrates library research withcognitive semantic analysis of classical and contemporary Qur'anicinterpretations (Ibnu Katsir and Al-Qurthubi), semi-structured interviews with 15prospective pilgrims from Kendari, and analysis of hajj policy documents.Cognitive semantic analysis using Fillmore's frame semantics and Sperber-Wilson's relevance theory reveals that istitha'ah is a multidimensional conceptencompassing physical, mental, financial, and spiritual capabilities, distinct fromsynonyms like qudrah. Research findings show that Kendari pilgrims haveinternalized holistic understanding of istitha'ah yet face complex challenges:health issues affecting 73% of pilgrims with comorbidities, financial barriers withhajj costs of IDR 46.2 million against local income of IDR 3.5 million monthly,and temporal constraints with waiting lists reaching 14-38 years. Holisticunderstanding of istitha'ah increases pilgrimage satisfaction by 52%, whereasnarrow interpretation causes social exclusion. The novelty of this research lies inthe first integration of cognitive semantic analysis of the Qur'an with localempirical data, demonstrating that istitha'ah is a dynamic concept requiringresponsive policies aligned with pilgrims' socioeconomic realities to ensure moreinclusive hajj accessibility.